What is Mera and its recognition in verses and traditions - Mohamad Hedayati (اخلاق وحیانی)
One of these harms that occurs in the context of dialogue is mara. . The aim of this research is to study the correct meaning of Mara based on the use of the Arabic word and its root meaning and also by using its use in verses and hadiths. The research hypothesis is that mara includes two important components of entering into another speech and wrist grip. The second hypothesis is that causes, effects and treatments have been mentioned for verses in the verses and hadiths. The third hypothesis is related to the ruling of Mara, which is absolutely reprehensible and ugly in ethics, but in jurisprudence there is a difference of opinion regarding its application and restriction and its condition and condition. The research is carried out with the information of lexicographers and verses of the Qur'an and the interpretation and collection of narrations and moral and jurisprudential analyzes based on verses and narrations. The purpose of this study is to identify what is relevant and its proper application in various areas of conversation ethics.